Alzheimer’s-like remodeling of neuronal ryanodine receptor in COVID-19 - Reiken, Steve (bioRxiv, 2021)
COVID-19, caused by SARS-CoV-2 involves multiple organs including cardiovascular, pulmonary and central nervous system. Understanding how SARS-CoV-2 infection afflicts diverse organ systems remains challenging (1,2) . Particularly vexing has been the problem posed by persistent organ dysfunction known as “long COVID,” which includes cognitive impairment (3) . Here we provide evidence linking SARS-CoV-2 infection to activation of TGF-ß signaling and oxidative overload. One consequence is oxidation of the ryanodine receptor/calcium (Ca (2+) ) release channels (RyR) on the endo/sarcoplasmic (ER/SR) reticuli in heart, lung and brains of patients who succumbed to COVID-19. This depletes the channels of the stabilizing subunit calstabin2 causing them to leak Ca (2+) which can promote heart failure (4,5) , pulmonary insufficiency (6) and cognitive and behavioral defects (7–9) . Ex-vivo treatment of heart, lung, and brain tissues from COVID-19 patients using a Rycal drug (ARM210) (10) prevented calstabin2 loss and fixed the channel leak. Of particular interest is that neuropathological pathways activated downstream of leaky RyR2 channels in Alzheimer’s Disease (AD) patients were activated in COVID-19 patients. Thus, leaky RyR2 Ca (2+) channels may play a role in COVID-19 pathophysiology and could be a therapeutic target for amelioration of some comorbidities associated with SARS-CoV-2 infection.